PQQ‐dependent Dehydrogenase Enables One‐pot Bi‐enzymatic Enantio‐convergent Biocatalytic Amination of Racemic sec‐Allylic Alcohols - Gandomkar, Somayyeh (ChemCatChem, 2020)
The asymmetric amination of secondary racemic allylic alcohols bears several challenges like the reactivity of the bi‐functional substrate/product as well as of the α,β‐unsaturated ketone intermediate in an oxidation‐reductive amination sequence. Heading for a biocatalytic amination cascade with a minimal number of enzymes, an oxidation step was implemented relying on a single PQQ‐dependent dehydrogenase with low enantioselectivity. This enzyme allowed the oxidation of both enantiomers at the expense of iron(III) as oxidant. The stereoselective amination of the α,β‐unsaturated ketone intermediate was achieved with transaminases using 1‐phenylethylamine as formal reducing agent as well as nitrogen source. Choosing an appropriate transaminase, either the (R)‐ or (S)‐enantiomer was obtained in optically pure form (>98 % ee). The enantio‐convergent amination of the racemic allylic alcohols to one single allylic amine enantiomer was achieved in one pot in a sequential cascade.